Blurring Boundaries: A Psychological Investigation into the Emotional Authenticity of Virtual Relationships in the 21st Century - Prasetyo, Erwin; Iftitah, Nur (Advances in Psychological Sciences and Applications, 2025)
With the increasing presence of digital communication, the distinction between virtual relationships and real-life interactions has become more blurred. The psychological effects of online relationships, especially in terms of emotional development and mental health, have garnered growing attention. This article explores the concept of virtual relationships and how they influence real emotions, drawing on existing literature to provide a comprehensive understanding of the topic. Using a conceptual framework, this study examines the complexities of virtual interactions and their psychological impact on individuals, particularly focusing on emotional authenticity, attachment, and social well-being. The methodological approach for this article is qualitative research. The primary research tool was a comprehensive literature review, focusing on psychological studies of virtual relationships, emotional development, and online communication patterns. The findings suggest that while virtual relationships may serve as meaningful substitutes, they are not a replacement for genuine human connections. Additionally, they may lead to emotional distress and distorted perceptions of intimacy, especially when they fail to fulfill essential emotional needs.